Dental Health Education Media in the Form of Android-Based Monopoly Game - Muliadi (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Introduction Oral and dental health problems can be prevented through dental health education in which methods and media play an important role. Media that is often used in schools is still conventional. So that it needs research on game-based media use. Aims To analyze the effectiveness of monopoly game as an android-based dental health education media. Methods Non-randomized control group Quasi-experimental pre-test and post-test design. Samples totaling 120 students (4 elementary schools) were taken using total sampling technique. The research instrument used was a questionnaire to evaluate the feasibility of the media and questionnaires to obtain the value of dental health knowledge and attitudes analyzed through Wilcoxon and Mann-Whitney tests. Results The p-value value of the comparative test of 2 groups in pairs on the knowledge and attitude of dental health in the intervention and control groups was 0.001. The p-value of the comparative test of 2 unpaired groups on dental health knowledge and attitudes between the intervention and control groups was 0.001. Conclusion The application of monopoly game is more effective than leaflets in improving knowledge, dental health attitudes and need further research to test the effectiveness with more sample sizes.